196k views
3 votes
How do I solve 3(x+1)=5(x−2)+7?

User Takasu
by
6.0k points

2 Answers

3 votes

Answer:

x = 3

Explanation:


3\left(x+1\right)=5\left(x-2\right)+7\\Expand\\3x+3 =5x -10+7\\Collect \:like\: terms\\3x-5x = -10+7-3\\-2x = -6\\Divide \:both\:sides\:of\:the\:equation\:by\:-2\\(-2x)/(-2) = (-6)/(-2)\\ \\x = 3

User Aneudi
by
4.9k points
1 vote

Answer:

x = 3

Explanation:

3(x+1)=5(x−2)+7

Use the distributive property to multiply 3 by x+1.

3x+3=5(x−2)+7

Use the distributive property to multiply 5 by x−2.

3x+3=5x−10+7

Add −10 and 7 to get −3.

3x+3=5x−3

Subtract 5x from both sides.

3x+3−5x=−3

Combine 3x and −5x to get −2x

−2x+3=−3

Subtract 3 from both sides.

−2x=−3−3

Subtract 3 from −3 to get −6.

−2x=−6

Divide both sides by −2.

x = -6/2

Divide −6 by −2

x = 3

User Wes Winder
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.